Pengaruh Kompensasi Finansial Terhadap Kinerja Karyawan Pada Kantor Koperasi - Albertina Gadi; Sisilia Susanti Lende; Mersiana Susanti Legi Bili; Emanuel Prido Wonga; Marlince Anastasia Bili (Pusat Riset dan Inovasi Nasional, 2024)
This reseach aims to determine the effect of financial compensation on the performance of savings and loan cooperative employees. The population studied was 32 employees who worked in the coopertive.The data collection technique used is by distributing questionnaires to all cooperative employees. The analysis technique used is simple linear regression analysis. The results of this research show that financia compensation influences the performance of savings and loan cooperative employees.